Bronchogenic Cyst: A Rare Cause of a Retroperitoneal Mass in a Neonate - Elahe Movahedi Moghadam; Mohammad Vasei; Amir Hossein Movahedian; Ziba Mosayebi (Mashhad University of Medical Sciences, 2021)
Background: Bronchogenic cysts (BCs) are congenital abnormalities of the primitive foregut, which are commonly found in the lung and mediastinum; however, they may rarely occur in the retroperitoneal region. Case report: We present a case of 20-day-old male newborn with a prenatal diagnosis of an abdominal mass who was referred and admitted to our hospital for further evaluation. Abdominal ultrasound and computed tomography scan demonstrated a retroperitoneal ill-defined solid mass locating on the upper ridge of the left kidney in close contact with the posterior wall of the stomach and pressure effects on the spleen hilum. Concerning presumptive diagnosis of neuroblastoma, less likely Wilms tumor, and subdiaphragmatic sequestration, surgery was carried out, and the mass removed completely. Pathological examination revealed a multiloculated cystic-solid mass with cystic spaces which was lined by respiratory epithelium, and the underlying fibrotic stroma contained islands of mature cartilage consistent with the diagnosis of bronchogenic cyst. Conclusion: Although BCs rarely occur, they should be considered in the differential diagnosis of a retroperitoneal mass in the neonates.   Keywords